Subsidence‐Derived Volumetric Strain Models for Mapping Extensional Fissures and Constraining Rock Mechanical Properties in the San Joaquin Valley, California. Issue 9 (11th September 2020) - Carlson, Grace; Shirzaei, Manoochehr; Ojha, Chandrakanta; Werth, Susanna
Abstract: Large‐scale subsidence due to aquifer‐overdraft is an ongoing hazard in the San Joaquin Valley. Subsidence continues to cause damage to infrastructure and increases the risk of extensional fissures.Here, we use InSAR‐derived vertical land motion (VLM) to model the volumetric strain rate due to groundwater storage change during the 2007–2010 drought in the San Joaquin Valley, Central Valley, California. We then use this volumetric strain rate model to calculate surface tensile stress in order to predict regions that are at the highest risk for hazardous tensile surface fissures. We find a maximum volumetric strain rate of −232 microstrain/yr at a depth of 0 to 200 m in Tulare and Kings County, California. The highest risk of tensile fissure development occurs at the periphery of the largest subsiding zones, particularly in Tulare County and Merced County. Finally, we assume that subsidence is likely due to aquifer pressure change, which is calculated using groundwater level changes observed at 300 wells during this drought. We combine pressure data from selected wells with our volumetric strain maps to estimate the quasi‐static bulk modulus, K, a poroelastic parameter applicable when pressure change within the aquifer is inducing volumetric strain. This parameter is reflective of a slow deformation process and is one to two orders of magnitude lower than typical values for the bulk modulus found using seismic velocity data. The results of this study highlight the importance of large‐scale, high‐resolution VLM measurements in evaluating aquifer system dynamics, hazards associated with overdraft, and in estimating important poroelastic parameters. Key Points: Models of volume strain rate are developed for the San Joaquin Valley during the 2007–2010 drought High risk of fissure initiation occurs on the periphery of subsiding zones based on the ratio of tensile stress to soil tensile strength The quasi‐static bulk modulus is estimated to be 0.19 GPa